Design and Validity of Electronic Assessments to Assess Students’ Creative Thinking Abilities on The Topic of Newton’s Laws - Rofifah Widara; Fatni Mufit; Yenni Darvina; Dea Stivani Suherman (Physics Learning and Education, 2025)
This study aims to develop and validate a comprehensive electronic assessment package to measure students' creative thinking abilities on the topic of Newton’s Laws. While creative thinking abilities are important to foster creativity, as one of 21st century skills, physics assessments often do not specifically measure this ability. This research addresses that gap by designing a complete and modern assessment system that uniquely integrates diagnostic, formative, and summative instruments into a single package. The study employed a Research and Development (R&D) method, adapting the Plomp model with a focus on the preliminary and prototyping stages. The feasibility of the product was tested through content validation by three experts, with the data analyzed using the Aiken's V index. The results show that all three instruments (diagnostic, formative, and summative), achieved a high validity category. In conclusion, the developed electronic assessment package is a valid and feasible instrument for comprehensively assessing creative thinking abilities in physics